Neural correlates of the risk for schizophrenia and bipolar disorder: a meta-analysis of structural and functional neuroimaging studies - Cattarinussi, Giulia; Kubera, Katharina Maria; Hirjak, Dusan; Wolf, Robert Christian; Sambataro, Fabio (Biological psychiatry, 2022)
Clinical features and genetics overlap in schizophrenia (SCZ) and bipolar disorder (BD). Identifying brain alterations associated with genetic vulnerability for SCZ and BD could help to discover intermediate phenotypes, quantifiable biological traits with greater prevalence in unaffected relatives (RELs), and early recognition biomarkers in ultrahigh risk populations. However, a comprehensive meta-analysis of structural and functional magnetic resonance imaging (MRI) studies examining relatives of patients with SCZ and BD has not been performed yet.